2022
DOI: 10.1007/s00167-022-07242-6
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting a second graft from the extensor mechanism for revision ACL reconstruction does not delay return of quadriceps function

Abstract: PurposeThe purpose of this study was to evaluate whether harvesting a second graft from the ipsilateral extensor mechanism adversely affects clinical outcomes in revision anterior cruciate ligament (ACL) reconstruction. MethodsA retrospective review of 34 patients undergoing revision anterior cruciate ligament (ACL) reconstruction with either quadriceps tendon (QT) autograft or bone–tendon–bone (BTB) autograft was conducted. Patients with two grafts (BTB+QT) from the extensor mechanism were matched based on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previously described extensor mechanism strength deficits associated with QT harvest appear less pronounced than originally thought; and while extensor strength is inferior to HT at 6 months, strength measurements are equivalent at 1 year [23, 29]. While concerns exist regarding a double hit to the extensor mechanism when using a BTB graft followed by a QT graft or vice versa, multiple studies have demonstrated there is no appreciable difference in extension strength with or without a use of a second extensor mechanism graft in RACLR [26, 56].…”
Section: Discussionmentioning
confidence: 99%
“…Previously described extensor mechanism strength deficits associated with QT harvest appear less pronounced than originally thought; and while extensor strength is inferior to HT at 6 months, strength measurements are equivalent at 1 year [23, 29]. While concerns exist regarding a double hit to the extensor mechanism when using a BTB graft followed by a QT graft or vice versa, multiple studies have demonstrated there is no appreciable difference in extension strength with or without a use of a second extensor mechanism graft in RACLR [26, 56].…”
Section: Discussionmentioning
confidence: 99%